Pelatihan Dokter Kecil Dalam Pemeliharaan Kesehatan Gigi Dan Mulut Pada Murid SDN 47 Kota Banda Aceh - Mardelita, Sisca; Keumala, Cut Ratna; Reca, Reca; Suryani, Linda; Mufizarni, Mufizarni (JEUMPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Peer Counselor Training in Dental Health Maintenance of Students at SD Negeri 47 Banda Aceh. The School Dental Health System (UKGS) is one of the most relevant health efforts in the implementation of the prevention of dental and oral diseases. This program is intended to improve the dental and oral health of all students in schools who need dental and oral health care. UKGS at SDN 47 Banda Aceh City is still less active due to the lack of facilities and infrastructure that support implementation. This Community Service aims to improve the skills of peer counselors in maintaining dental health at SDN 47 Banda Aceh so that they can provide an example to other SDN 47 students in maintaining oral and dental hygiene to achieve healthy living behaviors and improve the quality of human resources. Based on the results of community service at SDN 47 Banda Aceh City, it shows that the highest percentage of peer counselors' knowledge before training was in the unfavorable category, amounting to 14 people (70%), and after training on dental and improved good amounted to 20 people (100%). The conclusion from the results of this service is that there is an increase in the knowledge of peer counselors about maintaining dental and oral health, so it is hoped that peer counselors at SDN 47 Banda Aceh can apply this knowledge every day and teach back to friends at school. Keywords: Knowledge, peer counselor, maintenance of dental and oral hygiene.